Motives of Political Violence in the Middle East with Special Reference to Syria - Al-Fawwaz, Abdulrahman (Advances in Social Sciences Research Journal, 2018)
The study aims at understanding the concept of political violence and the reasons behind its spread in the Middle East, focusing on the study of the Syrian situation after the Baath Party took over since 1963 . The study has shown that the violence used in Syria is the official political violence practiced by the state against the people for the sake of perpetuation of the regime. The most important factors that led to the development of political violence in Syria represent the absence of political, social and economic justice, for the growth of internal opposition, notably the Muslim Brotherhood, which is one of the strongest political parties opposed to the Syrian regime. The study showed that the recent internal revolutions did not succeed due to the historical relations between the Syrian political system and Russia. The latter defended in various ways to maintain the Syrian regime and the position of the pro-regime Iran to achieve its strategic interests in the Arab world.